Potensi Tumbuhan Liar Patikan Kebo (Euphorbia hirta) Sebagai Tumbuhan Obat : Studi Literatur - Nir Fathiya; Ardhana Yulisma (Fakultas Teknik, 2023)
Patikan kebo (Euphorbia hirta) is a wild plant that has a long history as a medicinal herb throughout the world. This article is a review article that examines the potential of patikan kebo as a medicinal plant. The preparation of this article used literature studies from various scientific articles relating to the results of phytochemical screening, ethnobotany, and biological activity of patikan kebo reported in the last 10 years (20132023). This plant has secondary metabolite compounds that have been isolated from all its organs, such as flavonols, hydroxybenzoic acid, tannins, flavones, lignans, and mineral salts. Several studies have reported that the plant has biological and pharmacological activities such as antioxidant, anti-inflammatory, anticancer, antimicrobial, antidiabetic, antidiarrheal, antigout, diuretic, and toxicity. Patikan kebo is also safe to use based on its toxicity test. This review study can be used for the identification and preparation of a patikan kebo monograph. This shows that in the future, patikan kebo can be developed as a medicine from natural ingredients